1999
DOI: 10.3354/meps182119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trawling on seafloor habitat and associated invertebrate taxa in the Gulf of Alaska

Abstract: Short-term effects of bottom trawling on a 'hard-bottom' (pebble, cobble, and boulder) seafloor were studied on the outer continental shelf in the eastern Gulf of Alaska. Eight sites were trawled in August 1996; then, from a research submersible we videotaped each trawl path and a nearby reference transect to obtain quantitative data. Boulders were displaced, and large epifaunal invertebrates were removed or damaged by a single trawl pass. These structural components of habitat were the dominant features on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
111
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(114 citation statements)
references
References 15 publications
2
111
1
Order By: Relevance
“…Generally sessile species such as hydrozoans, bryozoans and sponges are more vulnerable to the impact of fishing gear than free-living species (Jennings & Kaiser 1998, Watling & Norse 1998, Freese et al 1999, Kaiser et al 2000. Unfortunately, there was little information on the presence of erect, sessile species, for example the horn wrack Flustra foliacea or dead man's finger Alcyonium digitatum.…”
Section: Nature Of Species Suffering From Declining Presencementioning
confidence: 99%
“…Generally sessile species such as hydrozoans, bryozoans and sponges are more vulnerable to the impact of fishing gear than free-living species (Jennings & Kaiser 1998, Watling & Norse 1998, Freese et al 1999, Kaiser et al 2000. Unfortunately, there was little information on the presence of erect, sessile species, for example the horn wrack Flustra foliacea or dead man's finger Alcyonium digitatum.…”
Section: Nature Of Species Suffering From Declining Presencementioning
confidence: 99%
“…Habitat destruction also occurs in marine systems, especially in more enclosed estuaries and embayments, but also in open coast unconsolidated habitats and coral reefs (Auster et al 1996, Watling and Norse 1998, Freese et al 1999, Edgar et al 2000. Historically, however, habitat destruction has probably been much less problematic along the open coast than on land.…”
Section: Threatening Processesmentioning
confidence: 99%
“…Mounting evidence indicates that the presence of sponges and corals enhances structural heterogeneity in otherwise low-relief environments and can lead to increases in biodiversity and abundance of associated animals (e.g., Tissot et al, 2006; Beazley et al., 2013; Knudby et al, 2013). The morphological features of these biogenic structures may also serve as refugia for different life stages of commercially harvested species of Sebastes (Freese and Wing, 2003;Rooper and Boldt, 2005; Baillon et al, 2012) and Atka mackerel (Pleurogrammus monopterygius) (Rand and Lowe, 2011) in Alaska waters.Previous studies have also shown putative associations of rockfishes with sponge, coral, and bryozoan assemblages across a wide range of physical and oceanographic conditions (Love et al, 1991;Rooper and Martin, 2012 to concentrate near the few boulders or rocky outcrops with attached epibenthic invertebrate communities (e.g., Freese and Wing, 2003; Du Preez and Tunnicliffe, 2011). The Pacific ocean perch has been the focus of several previous studies in Alaska, and there is strong evidence that postsettlement juveniles and adults of Pacific ocean perch are found associated with sponges and corals (Krieger, 1993; Brodeur, 2001;Rooper and Boldt, 2005;Rooper et al, 2007).…”
mentioning
confidence: 99%
“…Mounting evidence indicates that the presence of sponges and corals enhances structural heterogeneity in otherwise low-relief environments and can lead to increases in biodiversity and abundance of associated animals (e.g., Tissot et al, 2006; Beazley et al., 2013; Knudby et al, 2013). The morphological features of these biogenic structures may also serve as refugia for different life stages of commercially harvested species of Sebastes (Freese and Wing, 2003;Rooper and Boldt, 2005; Baillon et al, 2012) and Atka mackerel (Pleurogrammus monopterygius) (Rand and Lowe, 2011) in Alaska waters.…”
mentioning
confidence: 99%
See 1 more Smart Citation